2011
DOI: 10.1037/a0026145
|View full text |Cite
|
Sign up to set email alerts
|

The effects of valence and arousal on the emotional modulation of time perception: Evidence for multiple stages of processing.

Abstract: Previous research has demonstrated that both emotional valence and arousal can influence the subjective experience of time. The current research extends this work by (1) identifying how quickly this emotional modulation of time perception can occur and (2) examining whether valence and arousal have different effects at different stages of perception. These questions were addressed using a temporal bisection task. In each block of this task, participants are trained to distinguish between two different exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
7
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 51 publications
7
72
7
2
Order By: Relevance
“…the positive affect induced through the touch slowed down the children's internal timing mechanism making the waiting period seem shorter. Similar findings have been reported in the auditory domain by Droit-Volet et al (2013) who observed that pleasant music excerpts were judged as shorter than neutral excerpts of the same duration, and also in the visual domain (Angrilli et al, 1997;Buetti & Lleras, 2012;Smith, McIver, Di Nella, & Crease, 2011). Taken together with the current findings these studies suggest that positive affect has consistent shortening effects on temporal perception across sensory modalities.…”
Section: Discussionsupporting
confidence: 91%
“…the positive affect induced through the touch slowed down the children's internal timing mechanism making the waiting period seem shorter. Similar findings have been reported in the auditory domain by Droit-Volet et al (2013) who observed that pleasant music excerpts were judged as shorter than neutral excerpts of the same duration, and also in the visual domain (Angrilli et al, 1997;Buetti & Lleras, 2012;Smith, McIver, Di Nella, & Crease, 2011). Taken together with the current findings these studies suggest that positive affect has consistent shortening effects on temporal perception across sensory modalities.…”
Section: Discussionsupporting
confidence: 91%
“…For angry facial expressions this pattern has been replicated by the same research group and also, separate research groups (for a review see; Droit-Volet, 2013; Droit-Volet et al, 2013) using different tasks (Gil & DroitVolet, 2011). The overestimation effect generalizes to different types of emotional stimuli including emotional sounds (Noulhiane et al, 2007), aversively conditioned stimuli (Droit-Volet et al, 2010;Ogden et al, 2014), highly arousing negative images (Angrilli et al, 1997;Droit-Volet et al, 2011;Gil & Droit-Volet, 2012;Shi et al, 2012;Smith et al, 2011) and highly feared stimuli (Buetti & Lleras, 2012;Langer et al, 1961;Watts & Sharrock, 1984).…”
Section: Discussionmentioning
confidence: 87%
“…In several studies, only negative stimulus material was examined (Gil & DroitVolet, 2011Gil, Niedenthal, & DroitVolet, 2007;Grommet et al, 2011;Mella et al, 2011). In several other studies, different effects or effect sizes for positive and negative stimuli were observed (Angrilli et al, 1997;Doi & Shinohara, 2009;Droit-Volet et al, 2004;Effron et al, 2006;Noulhiane et al, 2007;Smith, McIver, Di Nella, & Crease, 2011;Tipples, 2008). Thus, for example, Effron et al (2006) and Tipples (2008) found that positive stimuli caused smaller effects than negative stimuli.…”
Section: Comparing Effects With Negative and Positive Stimulimentioning
confidence: 99%